Psychometric properties of the family communication scale in colombian population (2021)
Family communication establishes a vehicle for the transmission of information between family members and completely marks the nature and quality of family life. Family communication can be understood as an index of the climate and quality of the family system. Objective: To determine the psychometric properties of the Family Communication Scale of Olson et al. (1982) in its 20-item version. The participants were 934 Colombian university students between 18 and 35 years old. Method: A descriptive analysis of items and correlation with the scale was carried out, additionally a confirmatory factor analysis was carried out with the maximum likelihood method and varimax rotation. The internal consistency was evaluated using Cronbach’s alpha and McDonald’s Omega, followed by the analysis of the discrimination of the items through the biserial correlation coefficient. Results: The results indicate that the scale is reliable for its use in the Colombian population between 18 and 35 years old.